Partnerships and sustainable forest management: towards sustaining mahogany (Swietenia Macrophylla) in the Maya forest of Mexico and Belize - Snook, Laura K. (2003)
Mahogany has become the flagship species in debates about the feasibility of sustainable forest management in the tropics. Communities that own and control approximately 500,000 ha of permanent forest estate in Quintana Roo, Mexico, and an NGO that manages over 100,000 ha in neighboring Belize, have both made considerable progress towards implementing sustainable management of natural forests for mahogany production. Both types of forest managers are interested in the long term, rather than discounting their futures and choosing actions to maximize net present value. In part, their achievements reflect investments made by European bilateral and multilateral donors and American foundations. In addition, forest managers have sought collaboration with researchers to help them determine the best ways of achieving sustainability. Studies carried out under the leadership of CIFOR researchers on these production forests have revealed how silvicultural management can mimic natural disturbances that have favored the regeneration of stands rich in mahogany in the past. As a results of these partnerships, community and NGO forest owners are now in a position to demonstrate effective techniques for sustaining mahogany harvests that can be applied to forests elsewhere in Central and South America.